MATHEMATICAL MODELING OF HEAT TRANSFER THROUGH SINGLE-LAYER AND MULTI-LAYER CYLINDRICAL WALLS IN BUILDINGS AND STRUCTURES - Kuchkarbayev, Rustam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article presents an analysis of mathematical modeling processes for heat transfer in the walls of buildings and structures under current Uzbekistani conditions. The article also outlines the types of energy sources and the differences in the use of heat transfer processes during the construction of buildings, highlighting their main advantages and disadvantages.